2022
DOI: 10.1186/s41824-022-00153-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of lung cancer radiomics features extracted from data-driven respiratory gating and free-breathing flow imaging in [18F]-FDG PET/CT

Abstract: Background Quality and reproducibility of radiomics studies are essential requirements for the standardisation of radiomics models. As recent data-driven respiratory gating (DDG) [18F]-FDG has shown superior diagnostic performance in lung cancer, we evaluated the impact of DDG on the reproducibility of radiomics features derived from [18F]-FDG PET/CT in comparison to free-breathing flow (FB) imaging. Methods Twenty four lung nodules from 20 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(35 citation statements)
references
References 26 publications
(21 reference statements)
0
35
0
Order By: Relevance
“…13,31,34 The reproducibility rate of this study was as high as the SAM-based DDG-PET study that 131/141 (92.9%) image features had reproducibility. 30 The similar high reproducibility of PCAbased DDG-PET and SAM-based DDG-PET suggests the potential for interchangeability of texture features between other DDG-PET methods and NG-PET. In contrast, some texture features associated with GLRLM and GLZLM were not reproducible because these matrix indices, which are known to be highly variable, are calculated from large scales with many voxels.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…13,31,34 The reproducibility rate of this study was as high as the SAM-based DDG-PET study that 131/141 (92.9%) image features had reproducibility. 30 The similar high reproducibility of PCAbased DDG-PET and SAM-based DDG-PET suggests the potential for interchangeability of texture features between other DDG-PET methods and NG-PET. In contrast, some texture features associated with GLRLM and GLZLM were not reproducible because these matrix indices, which are known to be highly variable, are calculated from large scales with many voxels.…”
Section: Discussionmentioning
confidence: 89%
“…[22][23][24]37,38 Although several studies have demonstrated the reproducibility or variability between non-gated PET and external respiratory-gated PET methods, there are few studies on the novel DDG-based respiratory gating. [27][28][29][30] To the best of our knowledge, this is the first study to evaluate the reproducibility of PCA-based DDG on texture features in patients with NSCLC. In this study, total of 39/46 (84.8%) image features demonstrated repeatability based on adequate strength of agreement and non-significant variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations